Harnessing emotions to deliberative argumentation in classroom discussions on historical issues in multi-cultural contexts - Goldberg, Tsafrir; Schwarz, Baruch B. (Frontline Learning Research, 2016)
Abstract This theoretical paper is about the role of emotions in historical reasoning in the context of classroom discussions. Peer deliberations around texts have become important practices in history education according to progressive pedagogies. However, in the context of issues involving emotions, such approaches may result in an obstacle for historical clairvoyance. The expression of strong emotions may bias the use of sources, compromise historical reasoning, and impede argumentative dialogue. Coping with emotions in the history classrooms is a new challenge in history education. In this paper, we suggest that rather than attempting to foster positive emotion only or to avoid emotions all together, we should look at ways of engaging with emotion in history teaching. We present examples of peer deliberations on charged historical topics according to three pedagogical approaches that address emotions in different ways. The protocols we present open numerous questions: (a) whether facilitating engagement with own and the other’s emotions may lead to better processing of information and better deliberation of a historical question; (b) whether promoting national pride boosts reliance on collective narratives; and (c) whether adopting a critical teaching approach eliminates emotions and biases. Based on these examples and findings in social psychology, we bring forward working hypotheses according to which we suggest that instead of dodging emotional issues, teachers should harness emotions – not only positive but also negative ones, to critical and productive engagement in classroom activities.